Educational attainment and motor burden in Parkinson's disease. Issue 8 (10th June 2015) - Kotagal, Vikas; Bohnen, Nicolaas I.; Müller, Martijn L.T.M.; Koeppe, Robert A.; Frey, Kirk A.; Langa, Kenneth M.; Albin, Roger L.
ABSTRACT Objective Greater educational attainment is a protective factor for neurodegenerative dementias. If education earlier in life leads to greater cerebral reserve, it may play a similar protective role in Parkinson's disease (PD). Methods We conducted a cross‐sectional clinical imaging study of 142 subjects with PD. All subjects underwent [11C]dihydrotetrabenazine PET to confirm nigrostriatal dopaminergic denervation and brain MRI to estimate adjusted cortical gray matter volume (GMV). Results After adjusting for possible confounders, including cognitive and dopaminergic covariates, as well as nonspecific neurodegeneration covariates (age, disease duration, and total adjusted cortical GMV), lower years of education remained a significant predictor of higher total MDS‐UPDRS motor score (t = −3.28; P = 0.001). Education level associated inversely with white matter (WM) hyperintensities in a post‐hoc analysis (n = 83). Conclusions Higher educational attainment is associated with lower severity of motor impairment in PD. This association may reflect an extranigral protective effect upon WM integrity.